Potentials & Conditions of Remote Counselling of the Families of Children with Autism Spectrum Disorders - S.N. Pantsyr; E.F. Shvedovskiy (Moscow State University of Psychology and Education, 2020)
Remote psychological counseling with the use of telehealth technologies may be considered as one of the types of psychological and educational work with children. Due to the limitations of receiving full-time psychological and educational services, remote counseling may be the only available alternative support form for families of children with autism. This review of the Russian and international literature aims to reveal the general advantages and limitations of remote psycho-educational work and to identify existing protocols for conducting counseling. The data on studies in the field of online work with autistic children are presented. Concluded, that for successful online counseling of families of autistic children, four key conditions are necessary: professional qualities of a consultation provider, taking into account the family environment of the child, the presence of measurable characteristics of the intervention and the possibility of face-to-face interaction with the child.